A novel mechanism for the prevention of transcription replication conflicts. (4th May 2018) - Canal, Berta; Duch, Alba; Posas, Francesc; de Nadal, Eulàlia
ABSTRACT: Transcription and replication complexes can coincide in space and time. Such coincidences may result in collisions that trigger genomic instability. The phosphorylation of Mrc1 by different signaling kinases is part of a general mechanism that serves to delay replication in response to different stresses that trigger a massive transcriptional response in S phase. This mechanism prevents Transcription-Replication Conflicts and maintains genomic integrity in response to unscheduled massive transcription during S phase.